2017
DOI: 10.1007/s00792-017-0958-7
|View full text |Cite
|
Sign up to set email alerts
|

Delignification and detoxification of peanut shell bio-waste using an extremely halophilic laccase from an Aquisalibacillus elongatus isolate

Abstract: Lignocellulose bioconversion is a harsh process requiring the use of surfactants and organic solvents. Consequently, the incorporation of laccases in this bioconversion requires the bioprospecting of enzymes that can remain stable under extreme conditions. An extracellular, highly stable laccase was produced by the halophilic isolate Aquisalibacillus elongatus in submerged liquid culture fermentation. Statistical and non-statistical strategies gave the highest enzymatic activity (8.02 U mL) following addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…[ 56 ] and Natrialba magadii [ 57 ]. However, only few cellulases [ 58 , 59 , 60 ] and laccases [ 61 , 62 ] producing halophiles have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] and Natrialba magadii [ 57 ]. However, only few cellulases [ 58 , 59 , 60 ] and laccases [ 61 , 62 ] producing halophiles have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Halophiles bacteria are quite interesting due to the uncommon resistance to high saline levels, a feature usually linked to remarkable tolerance to UV light radiations, temperature, and extreme pH values. Actually, Penicillium chrysogenum, isolated in saline soil, has the capability to depolymerize lignin directly on olive milled substrate from oil production [48]; meanwhile, several halophilic ligninolytic enzymes were isolated and tested on raw substrates such as sugar beet pulp [49], almond shells [50] or peanut shells [51]. All these microorganisms, and related enzymes, were tested successfully on such substrates with minimal or no pre-treatment.…”
Section: Extremophilic Microorganismsmentioning
confidence: 99%
“…158 Al-Zuhair et al investigated the enzymatic delignification of seaweed biomass (a mix of Chaetomorpha and Cladophora species), carried out using TvL, HBT, and [EMIM][OAc] obtaining a delignification degree up to 27%. 162 Rezaei et al reported the use of LC from the halophilic bacterium Aquisalibacillus elongatus in the presence of [BMIM]-[PF 6 ] (1-butyl-3-methylimidazolium hexafluorophosphate) to delignify sugar beet pulp, obtaining a delignification yield of 78.4% after 24 h. 163 The same enzyme was also tested in the same conditions in [BMIM][PF 6 ] to remove lignin from peanut shell, obtaining a lignin removal of 87% after 24 h. 164 Deep Eutectic Solvents. Deep eutectic solvents (DESs) are a new class of green solvents composed of a hydrogen bond acceptor (HBA, usually a quaternary ammonium salt) and a hydrogen bond donor (HBD) such as glycerol, succinic acid, etc.…”
Section: Acs Sustainablementioning
confidence: 99%
“…Rezaei et al reported the use of LC from the halophilic bacterium Aquisalibacillus elongatus in the presence of [BMIM]­[PF 6 ] (1-butyl-3-methylimidazolium hexafluorophosphate) to delignify sugar beet pulp, obtaining a delignification yield of 78.4% after 24 h . The same enzyme was also tested in the same conditions in [BMIM]­[PF 6 ] to remove lignin from peanut shell, obtaining a lignin removal of 87% after 24 h …”
Section: Delignification Main Strategies and Protocolsmentioning
confidence: 99%